WOX14 promotes bioactive gibberellin synthesis and vascular cell differentiation in Arabidopsis. (26th March 2017) - Denis, Erwan; Kbiri, Nadia; Mary, Viviane; Claisse, Gaëlle; Conde e Silva, Natalia; Kreis, Martin; Deveaux, Yves
Summary: Procambial and cambial stem cells provide the initial cells that allow the formation of vascular tissues. WOX4 and WOX14 have been shown to act redundantly to promote procambial cell proliferation and differentiation. Gibberellins (GAs), which have an important role in wood formation, also stimulate cambial cell division. Here we show that the loss of WOX14 function phenocopies some traits of GA‐deficient mutants that can be complemented by exogenous GA application, whereas WOX14 overexpression stimulates the expression of GA3ox anabolism genes and represses GA2ox catabolism genes, promoting the accumulation of bioactive GA. More importantly, our data clearly indicate that WOX14 but not WOX4 promotes vascular cell differentiation and lignification in inflorescence stems of Arabidopsis. Significance Statement: Vascular stem cell proliferation and differentiation involve many signaling pathways. WOX genes play a central role in these processes. The data presented here indicate that WOX14 promotes bioactive GA biosynthesis during stem maturation in Arabidopsis and underline the complex interplay between WOX genes and hormonal cues that occurs during wood formation.